Análise de recursos e usos das empresas beneficiadas pelo Fundo de Desenvolvimento Industrial – FDI/Ceará - Araújo, Diego Santana de (2024)
This paper seeks to detail the main concepts related to the structure of the National Accounts System of the Brazilian economy, and in particular, the Table of Resources and Uses of the Ceará economy. It also analyzes the main characteristics of the Ceará Industrial Development Fund (FDI) and some of the amounts applied through the program. And mainly, it seeks to draw comparisons between the profiles of use of intermediate goods by the benefited companies, using data from tax records, and the same profile in the respective sectors of the Ceará economy, based on the Table of Resources and Uses of the state of Ceará from 2013. The results do not present evidence that the companies in the manufacturing industry benefited have different input uses than the sector as a whole, but there is relevant evidence for the other sectors, with lower participation in the FDI.